2000
DOI: 10.1016/s0377-1237(17)30084-9
|View full text |Cite
|
Sign up to set email alerts
|

Stress Fractures: Effect of Prior Physical Activity, Sports Participation and Military Training

Abstract: A study was carried out to fmd out the effects of prior physical activity, sports participation and prior military training on the incidence of stress fractures among Gentlemen Cadets (GC's) undergoing military training at Indian Military Academy (IMA). One thousand and fourteen GC's were followed up for a period of 12 weeks. Thirty-seven GC's developed stress fractures during the study period. The incidence of stress fractures was significantly higher in GC's without any prior military training (p=0.0009). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…This study yields a similar result as observed by Singh et al 18 In our study it is interesting to observe that the incidence of SF increases (5.89%) in recruits with history of no physical activity in comparison to recruits with history of physical activity (5.05%). Prior physical activity reduced the incidence of SF 18 as the study is compared between technical and non-technical graduates from Indian Military Academy (IMA). Physical and sports activities before joining army training in a regimental centre significantly influenced SF in our study.…”
Section: Conflicts Of Interestsupporting
confidence: 92%
See 2 more Smart Citations
“…This study yields a similar result as observed by Singh et al 18 In our study it is interesting to observe that the incidence of SF increases (5.89%) in recruits with history of no physical activity in comparison to recruits with history of physical activity (5.05%). Prior physical activity reduced the incidence of SF 18 as the study is compared between technical and non-technical graduates from Indian Military Academy (IMA). Physical and sports activities before joining army training in a regimental centre significantly influenced SF in our study.…”
Section: Conflicts Of Interestsupporting
confidence: 92%
“…the basic phase of training similar to the study by Giladi et al 17 The distribution of sites of SF in this study is similar to the other military studies. 19,21 The most affected bone is tibia and the common site of tibial involvement is the upper one-third which is similar to Orava et al and Singh et al 18 The lower one-third SF of tibia is common amongst recruits having mild knock knee. In our series, it was decided to study whether the intercondylar distance (relative bow leg) made any significant difference to the site of SF.…”
Section: Disposal and Outcome Of All Stress Fracture Cases After Hospmentioning
confidence: 52%
See 1 more Smart Citation
“…The distribution of sites of SF in this study is similar to the study by Singh SC, et al, [9]. However, in contrast Alexander M Wood et al, reported metatarsals as the most common site for stress fracture [3].…”
Section: Methodssupporting
confidence: 87%
“…15 However, the incidence of SFs in this study was found to be 2.3% which was similar to an Indian study published by Singh et al who reported the incidence of SFs as 3.65%. 19 For the purpose of classification of SFs, we used a classification system as proposed in the study by Agarwal (Table 1). Similar classification system has been used in a study by Dash et al In their study, they found that the most common grade of SFs was Grade II followed by Grade I.…”
Section: Discussionmentioning
confidence: 99%